Identifying resilience principles in the UK air transportation industry and developing an integrated conceptual resilience framework. - Steinmann, Fabian (Cranfield University, 2022)
Organisations across the aviation sector strive to become more resilient, and there is a great desire to integrate resilience into the operation. However, there is no clear definition of resilience, and people in academia and industry have interpreted the concept differently. The research aims to integrate different conceptualisations of resilience and develop a framework that holistically explains how resilience can be developed in the UK air transportation industry context. The development of the framework is achieved through an integration of the literature and empirical refinement of the subsequent preliminary framework. A systematic, multi-sector and cross-disciplinary literature review was conducted to determine four main themes of resilience: System Design, System Preparedness, System Response, and System Changes. A total of 26 high-level resilience principles were identified in the literature and grouped into different (sub-)themes, building the foundation for a Preliminary Resilience Framework (PRF). The empirical work of the thesis investigated five cases in the UK air transportation system. The qualitative research aimed to identify empirical evidence through thematic analysis of how the UK air transportation industry operationalised the identified high-level principles. The analysis of the cases found evidence for 19 of the 26 principles. Furthermore, the case study findings determined ten new connections between the various identified (sub-)themes and refined the PRF. The five case study findings were synthesised to develop an Integrated Conceptual Resilience Framework (ICRF). The ICRF combines findings from all five case studies and provides a holistic resilience framework, outlining the principles and features of a resilient UK air transportation system.
Keywords: Resilience engineering; IRG; system; setup; checks; preparedness; robustness; rebound; extensibly; changes